External power competition in the Horn of Africa - Ylönen, A. (RUSI Journal, 2022)
External power competition in the Horn of Africa is intensifying. In recent years, the US and China, as well as regionally powerful states such as Saudi Arabia, Turkey, the UAE and Qatar, have all deepened their involvement in the sub-region. This has opened new opportunities for state and non-state actors in the Horn to gain influence through financial and material resources by associating themselves with external powers. Somaliland is one such actor. In the current scenario, Hargeisa’s increasingly sophisticated foreign policy has enabled it to step up its quest for international recognition and development. In this article, Aleksi Ylönen discusses the increasing contestation of influence among external powers in the Horn of Africa and Somaliland’s position in this changing regional context.